Gender And The Development Of A Positive School Culture And Academic Excellence - Muzvidziwa, Irene (School of Social Work, 2021)
This paper reflects on the influences of gender in developing a culture of academic excellence in schools. This paper is based on a case study of Janet a primary school principal in KwaZulu Natal, South Africa. The case study is drawn from a larger sample of a study based on an in-depth qualitative research design. Information generated from the primary school principal was solicited using interviews. Emphasis was on richness of data and uniqueness of the case. The findings were characterised by the spirit of team work, community involvement, hunhu/ubuntu and a learning culture.